KINERJA TUTOR DALAM PELAKSANAAN PEMBELAJARAN KESETARAAN PAKET C DI PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Miranti, Amanda; Jas, Jaspar; Maemunaty, Tity (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This studyaims to determinethe high performance tutors learning in the implementation of the equality package C in community learning center (PKBM) Rumbai Pesisir Districts of Pekanbaru City.The research question guiding this study is: how high the level of performance in the implementation of tutors learning equality package C in community learning center (PKBM) Rumbai Pesisir District of Pekanbaru City?. This is a descriptive study, data were collected using a questionnaire shaped instrument number 43 point statement. Once tested, the questionnaire is valid as much as 36 grains, and is invalid as much as 7 grains. Overall declared valid instrument with